Review of extremity dosimetry in nuclear medicine. (6th December 2021) - Kollaard, Robert; Zorz, Alessandra; Dabin, Jérémie; Covens, Peter; Cooke, Jennie; Crabbé, Melissa; Cunha, Lidia; Dowling, Anita; Ginjaume, Mercè; McNamara, Leanne
Abstract: The exposure of the fingers is one of the major radiation protection concerns in nuclear medicine (NM). The purpose of this paper is to provide an overview of the exposure, dosimetry and protection of the extremities in NM. A wide range of reported finger doses were found in the literature. Historically, the highest finger doses are found at the fingertip in the preparation and dispensing of 18 F for diagnostic procedures and 90 Y for therapeutic procedures. Doses can be significantly reduced by following recommendations on source shielding, increasing distance and training. Additionally, important trends contributing to a lower dose to the fingers are the use of automated procedures (especially for positron emission tomography (PET)) and the use of prefilled syringes. On the other hand, the workload of PET procedures has substantially increased during the last ten years. In many cases, the accuracy of dose assessment is limited by the location of the dosimeter at the base of the finger and the maximum dose at the fingertip is underestimated (typical dose ratios between 1.4 and 7). It should also be noted that not all dosimeters are sensitive to low-energy beta particles and there is a risk for underestimation of the finger dose when the detector or its filter is too thick. While substantial information has been published on the most common procedures (using 99m Tc, 18 F and 90 Y), less information is available for more recent applications, such as the use of 68 Ga for PET imaging. Also, there is a need for continuous awareness with respect to contamination of the fingers, as this factor can contribute substantially to the finger dose.